KONFLIK BATIN TOKOH DALAM CERPEN “KEBAHAGIAAN YANG MEMBUNUH” KARYA ATTA VERIN: KAJIAN PSIKOANALISIS SIGMUND - Nagita Ayu Windorika; Eni Nurhayati; Mohammad Rokib; Alya Ragil Ramadhani; Isti Choirunnisa Zalsabila; Silviana Putri Ema Susanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the inner conflict and personality dynamics of the main character in Atta Verin's short story "Happiness that Kills" through Sigmund Freud's psychoanalytic approach. Using descriptive qualitative methods, the study results reveal tension between the main character's id, ego, and superego in balancing personal desires and moral demands as a mother. The use of defense mechanisms such as denial and repression is also found. The study concludes that the character's happiness is ironic and destructive, as revealed through an in-depth analysis of her psychological structure.